1068 Severe Central Sleep Apnea in a Pediatric Patient with Klippel-Feil Syndrome. (12th April 2019) - Goldman, L; Hassan, F
Abstract: Introduction: Klippel-Feil Syndrome is characterized by congenital fusion of cervical vertebrae as well as bony abnormalities such as scoliosis and Sprengel deformity (failure of the scapulae to descend to the proper position), genitourinary, and cardiovascular anomalies. Its incidence is estimated at 1:40, 000–42, 000 live births. Rarely, Kippel-Feil syndrome can be associated with spinal stenosis and Chiari malformation with resulting hydrocephalus causing posterior fossa compression and sleep disordered breathing. Report of Case: A 7-year old female with a past medical history of Klippel-Feil Syndrome, Sprengel deformity, scoliosis (32 degree levo-convex cervicothoracic curve), and MURCS (mullerian duct aplasia, unilateral renal aplasia, and cervicothoracic somite dysplasia) presented to our pediatric sleep disorders clinic with an established diagnosis of central sleep apnea with a central apnea index (CAI) of 196 events per hour on a baseline study that was initially treated with supplemental oxygen, followed by treatment with adaptive servo-ventilation at an outside facility. The patient underwent foramen magnum decompression and laminectomy at 3 years of age due to MRI findings of a tight cranio-cervical junction, syrinx, and foramen magnum compressing the brainstem in the context of bradycardic episodes requiring admission to the intensive care unit. At our initial clinic visit, we ordered a split-night polysomnogram with transcutaneous-CO2 monitoring. The baseline portion of the study demonstrated severe central sleep apnea (CAI = 46.2, oxygen saturation nadir 74%) without hypoventilation. During the titration portion of the study, bilevel PAP with back-up rate did not effectively treat the central apnea, however average volume assured pressure support ventilation (AVAPS) treated the patient's sleep disordered breathing. Conclusion: This report highlights the importance of testing for sleep disordered breathing, specifically, central sleep apnea, in patients with Klipple-Feil Syndrome. Furthermore, it also highlights the importance of close clinical monitoring, even following neurosurgical interventions, as these interventions may not be curative of the underlying sleep disorder.